Phytochemical prospecting of the methanolic extract of leaves of the Species Cymbopogon Citratus / Prospecção fitoquímica do extrato metanólico das folhas da Espécie Cymbopogon Citratus - Anderson Soares de Almeida; Aldenir Feitosa dos Santos (Universidade Estadual de Alagoas, 2018)
From the beginnings of mankind man sought the relief of his evils with ingestion of herbs and plants. Nowadays, the study of the compounds produced in the secondary metabolism of plants is growing, since they have a variety of beneficial effects on the organism. The present work aimed to perform the phytochemical study of the leaves of the holy grass through phytochemical screening, this method is based on the change in coloration of precipitate formation of the plant extracts with certain specific reagents. The leaves were collected crushed and the constituents were extracted by maceration in methanol, the dry extract by route-evaporation. Flavones, flavonols, xanthones and saponins have been identified, these classes of compounds have antioxidant and antifungal action. Therefore, new advanced studies should be performed with other fractions of the species for new drug discovery.